FAKTOR YANG BERHUBUNGAN DENGAN KELANGSUNGAN HIDUP BAYI YANG DIRAWAT DI RUMAH SAKIT UMUM DAERAH KABUPATEN LABUHAN BATU UTARA TAHUN 2012 - Anastasya Desi O Napitupulu; Yusniwarti Yusad; Abdul Jalil Amri Arma (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
The fourth purpose of the Millennium Development Goals (MDGs) is to reduce child mortality where the target is to reduce under 5 years old mortality, Indonesia continues to improve child health as indicated by the decline in under 5 years old mortality, infant and neonatal. This study aims to analyze the relationship between the survival of infants with maternal factors (age, parity, spacing births) and infant factors (age, breast feeding, illness, nutrition and immunization status). This was an observational study using secondary data (medical records) from January 1 to December 31, 2012 in babies admitted to RSUD Kabupaten Labuhan Batu Utara. Data were analyzed by Chi Square test with α = 0,05. The results showed that the number of infant deaths in RSUD Kabupaten Labuhan Batu Utara as 17 infants in which the factors associated with infant survival is a parity (p = 0, 015) and nutrition (p = 0,001). It is expected that the parties and the relevant agencies in order to improve the counseling to mothers whose babies were cared for and improving health care in particular maternal and child health services to prevent and reduce infant mortality. Keywords: Survival of infant thread, maternal factors, infant factors